Towards developing a decision support system for strategic investment applications - Moskalenko, V. V.; Zakharova, T. V. (NTU "KhPI", 2008)
In this paper the investment decision support system is offered. This system gives the opportunity of estimation of the efficiency and risk of investment projects. The system can also carry out the sensitivity analysis of the investment project working out the recommendations for increasing the efficiency of the project and portfolio foundation.

В даній статті пропонується система підтримки прийняття інвестиційних рішень. Ця система дає можливість оцінки ефективності та ризику інвестиційних проектів. Також система має можливість провести аналіз чутливості інвестиційного проекту, розробляючи рекомендації по збільшенню ефективності та зменшенню ризику проекту та формування портфелю.
Keywords: інвестиційні проекти; ризики; система підтримки; прийняття рішень